An analysis of country governance impact to the revenue efficiency of Islamic and conventional banks in GCC countries - Kamarudin, Fakarudin; Sufian, Fadzlan; Md. Nassir, Annuar (2016)
The paper provides new empirical evidence on the impact of country governance on the revenue efficiency of Islamic and conventional banks. The empirical analysis is confined to Islamic and conventional banks operating in the Gulf Cooperation Council (GCC) countries banking sectors during the period of 2007 to 2011. The analysis comprise of two main stages. In the first stage, we employ the Data Envelopment Analysis (DEA) method to compute the revenue efficiency of individual Islamic and conventional banks. We then employ panel regression analysis to investigate the effect of country governance on revenue efficiency. The empirical findings indicate that greater voice and accountability, government effectiveness, and rule of law enhance the revenue efficiency of both Islamic and conventional banks. We find that regulatory quality exerts positive influence on Islamic banks, while the impact of political stability and control of corruption enhances the revenue efficiency of conventional banks.